Efek warna cahaya terhadap tingkah laku dan kanibalisme pada benih ikan kerapu cantang (Epinephelus fuscoguttatus lanceolatus) - Koten, Antonius Paulus Mariano; Lukas, Ade Yulita Hesti; Ratoe Oedjoe, Marcelien Dj (Jurnal Aquatik, 2024)
This research was experimental in nature which was carried out by observing the response and behavior of cantang grouper to the color of the light. The research was carried out by spreading food in containers with different colored lights. From the food spread in containers with different lights, we can see the response and behavior shown by the cantang grouper to each color of light. Apart from that, research was also carried out to determine the level of cannibalism and mortality rates in each container with different lights. This research is using experimental method. The research design used was a Completely Randomized Design (CRD), with 4 treatments and 3 replications using blue, yellow-green and no light. The research was carried out by measuring water quality 3 times a day, starting in the morning, afternoon and evening for 14 days of research. The conclusion of the research is that outside its natural habitat the best response and behavior is when living in a blue treatment container (treatment A). It is thought that in blue light the cantang grouper feels like it is in its natural habitat. Apart from that, blue light also reduces the level of cannibalism in cantang grouper fish compared to green and yellow light, and no light. Keywords: Light, cantang grouper, cannibalism, mortality, behavior.